DEVELOPMENT OF AUGMENTED REALITY MEDIA FOR AUTOMATION OF MANAGEMENT OF OFFICE FACILITIES AND INFRASTRUCTURE IN VOCATIONAL HIGH SCHOOLS - Putri, Lavia Meiras; Faslah, Roni; Marsofiyati (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
This study aims to develop Augmented Reality (AR)-based learning media called "kantAR" and measure its feasibility level for the subject of Automation of Office Facilities and Infrastructure Management at SMKN 48 Jakarta. The background of this study is the existence of problems in the learning process, such as monotonous media and students' difficulties in visualizing abstract office equipment in textbooks. The research method used is Research and Development (R&D) by adopting the 4D model consisting of the Define, Design, Develop, and Disseminate stages. The results of the study showed that the "kantAR" learning media obtained an average feasibility percentage of 89.5% from material experts and media experts, which is included in the "very feasible" category. Furthermore, the results of the trial on students in the one-to-one evaluation stage obtained a score of 99% and the small group evaluation stage obtained a score of 91%, both of which showed the "very practical" category. Thus, it is concluded that the AR media "kantAR" is very feasible and practical to be implemented as an innovative and interactive learning solution to improve student understanding.